ORTHODOX CHURCH ARCHITECTURE IN THE NORTHERN DISTRICTS OF CYPRUS FROM THE MID-19TH CENTURY TO 1974 FROM ECLECTICISM TO NEO-BYZANTINE - Kiessel, Marko; Tozan, Asu (Univ Zagreb Fac Architecture, 2014)
This paper analyses Orthodox Church architecture in Cyprus, considering building typology and sculptural decoration. The hybrid character of the initial eclecticism may be understood as reflection of Cypriot identity. The subsequent dominance of the Neo-Byzantine style began when the aspirations of Greek-Cypriots for Enosis turned into an anti-colonial movement. The Neo-Byzantinism can be understood as expression of Greek cultural-religious identity.
Keywords: ARCHITECTURAL DECORATION; CHURCH ARCHITECTURE; CYPRUS; ECLECTICISM; NEO-BYZANTINISM